Gambaran Stres Kerja yang Disebabkan oleh Peran Ganda serta Hubungan antara Work-Family Conflict dan Work-Family Balance pada Ibu Bali Bekerja - Ni Putu Trisca Wisuda Putri; Robertus Landung Eko Prihatmoko (Fakultas Psikologi Universitas Sanata Dharma, 2022)
This study aims to describe job stress caused by multiple roles and the relationship between work-family conflict and work-family balance in working Balinese mothers. The independent variable in this study is work-family conflict, while the dependent variable in this study is work-family balance. This study has one hypothesis, this hypothesis is that work-family conflict has a negative and significant relationship to work-family balance. This type of research is mixed methods research, which combines qualitative research methods and quantitative research. This study uses a convenience sampling technique. The subjects of this are women who are Hindu, live in Bali, and carry out the roles of mother, wife, work, and krama adat, totaling 388 people. The scale used in this study is a scale that has been adapted from Carlson et al. (2000) for work-family conflict variables with a reliability of 0.87 for time-based WIF, 0.79 for time-based FIW, 0.85 for strain-based WIF, 0.87 for strain-based FIW, 0.78 for behavior-based WIF, and 0.85 at behavior-based FIW. In addition, the scale used for the work-family balance variable was adapted from Bintang and Astiti (2016) with a reliability of 0.911. The scale is filled by the subject in a self-report. The analysis technique used for qualitative data is thematic analysis techniques with MAXQDA 2018 tools. The result of qualitative research is that work-family conflict is one of the causes of work stress in working Balinese mothers. In quantitative data, non-parametric correlation analysis techniques are used with SPSS for windows version 22. The results of the analysis that have been carried out show that there is a negative and significant relationship between work-family conflict and work-family balance. This means, the higher the level of work-family conflict in an individual, the lower the level of work-family balance in that individual. The results of quantitative research can also be used to see the level of work stress in working Balinese mothers, namely Balinese mothers working in this study have a low level of work stress. Keywords: Work-Family Conflict, Work-Family Balance, Job Stress